2020
DOI: 10.4143/crt.2019.119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Significant Prognostic Tissue Markers Associated with Survival in Upper Urinary Tract Urothelial Carcinoma Patients Treated with Radical Nephroureterectomy: A Retrospective Immunohistochemical Analysis Using Tissue Microarray

Abstract: The purpose of this study was to identify prognostic tissue markers for several survival outcomes after radical nephroureterectomy among patients with upper urinary tract urothelial carcinoma using tissue microarray and immunohistochemistry. Materials and Methods Retrospectively, data of 162 non-metastatic patients with upper urinary tract urothelial carcinoma after radical nephroureterectomy between 2004 and 2016 were reviewed to determine intravesical recurrence-free survival (IVRFS), disease-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…All the studies adopted immunohistochemistry (IHC) to analyze the level of PD-L1 in tumor tissues. Notably, the intensity of PD-L1 in IHC was only mentioned in four studies (14,(23)(24)(25), while none of them reported neither the mean/median intensity nor its linear correlation with the outcomes. The NOS grades indicated that all studies had high qualities (Supplementary Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies adopted immunohistochemistry (IHC) to analyze the level of PD-L1 in tumor tissues. Notably, the intensity of PD-L1 in IHC was only mentioned in four studies (14,(23)(24)(25), while none of them reported neither the mean/median intensity nor its linear correlation with the outcomes. The NOS grades indicated that all studies had high qualities (Supplementary Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…We excluded records for the following reasons: article types or not relevant topics (n = 188), studies had few study samples (≤50) or follow-up duration less than 12 months (n = 4), not in English (n = 9), or insufficient survival data (n = 15). Finally, we included eight retrospective cohort studies (1,406 individuals) (13)(14)(15)(16)(17)(23)(24)(25) in the study (shown in Figure 1).…”
Section: Literature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] In addition, several molecular proteins have not only been investigated for their potential as prognostic factors but are also associated with IVR in patients with UTUC, showing the relevance of molecular biology findings in clinical practice. 30 Huang et al 31 suggested that the high expression of amplified in breast cancer 1, a human oncogene, is involved in a number of biological processes, such as cell proliferation, cell migration, and cell differentiation. In addition, eukaryotic initiation factor 5A2, which is also classified as an oncogene and an independent molecular marker for shorter survival time in patients with bladder cancer treated with radical cystectomy, is a risk factor for IVR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, postoperative single‐dose intravesical chemotherapy after nephroureterectomy has been recommended, as it significantly reduces the likelihood of IVR 27–29 . In addition, several molecular proteins have not only been investigated for their potential as prognostic factors but are also associated with IVR in patients with UTUC, showing the relevance of molecular biology findings in clinical practice 30 . Huang et al 31 .…”
Section: Discussionmentioning
confidence: 99%